Analisis Implementasi Kebijakan Inovasi Program Gerakan IT (GENIT) untuk Meningkatkan Kualitas Siswa di Sekolah Dasar - Fauzia, Azhar Syifa; Maharani, Ajeng Putri; D, Deborah; Hutabarat, Keren Hapug; Zulfikar, Muhammad; Azzahra, Naufia Nurzakiyyah; Alindra, Afridha Laily (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of the innovation policy of the IT Movement Program (GENIT) in improving the quality of students in one of the elementary schools in Purwakarta Regency. The background of this research is the importance of integrating information technology in primary education to equip students with 21st century skills. The method used is qualitative, with data collection techniques in the form of interviews with teachers and closed questionnaires to students. The results show that technology development policies, including the provision of digital devices and teacher training, have improved interactivity and learning effectiveness. The GENIT program as an extracurricular activity has been proven to encourage the improvement of student achievement in the field of technology. Despite challenges such as lack of student participation in technology activities, parental involvement and school policy support play an important role in successful implementation. This study concludes that collaboration between schools, teachers, students, and parents, as well as structured policy planning, is key in creating an adaptive and competitive quality of education in the digital age.